2013
DOI: 10.1186/1471-2164-14-113
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of palatal transcriptome to identify cleft palate genes within TGFβ3-knockout mice alleles: RNA-Seq analysis of TGFβ3 Mice

Abstract: BackgroundIn humans, cleft palate (CP) accounts for one of the largest number of birth defects with a complex genetic and environmental etiology. TGFβ3 has been established as an important regulator of palatal fusion in mice and it has been shown that TGFβ3-null mice exhibit CP without any other major deformities. However, the genes that regulate cellular decisions and molecular mechanisms maintained by the TGFβ3 pathway throughout palatogenesis are predominantly unexplored. Our objective in this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 74 publications
1
49
0
Order By: Relevance
“…These, in parallel with the transcription factors Snai1 and Snai2, promote MES apoptosis and disintegration. 6,21,[39][40][41][42][43] Our results demonstrated that not only the Tgfβ-pathway genes but also other pathway-related genes might interact each other to regulate medial edge epithelium disintegration and complete palatogenesis (Supplementary Figure 2) In several studies, it has been suggested that there is a gene-environment interaction exists between smoking and TGFα expression for the induction of cleft palate. 8,25,[44][45][46][47][48][49] By using our microarray analysis and filtering cleft palate-related genes, we determined that nicotine is the highly susceptible element of smoking to induce down-regulation of TGFα, which may explain the palatal size abnormality observed in nicotine-treated pups.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These, in parallel with the transcription factors Snai1 and Snai2, promote MES apoptosis and disintegration. 6,21,[39][40][41][42][43] Our results demonstrated that not only the Tgfβ-pathway genes but also other pathway-related genes might interact each other to regulate medial edge epithelium disintegration and complete palatogenesis (Supplementary Figure 2) In several studies, it has been suggested that there is a gene-environment interaction exists between smoking and TGFα expression for the induction of cleft palate. 8,25,[44][45][46][47][48][49] By using our microarray analysis and filtering cleft palate-related genes, we determined that nicotine is the highly susceptible element of smoking to induce down-regulation of TGFα, which may explain the palatal size abnormality observed in nicotine-treated pups.…”
Section: Discussionmentioning
confidence: 63%
“…22 Gene targeting to knock-out specific genes in mice has generated, by the date, 84 lossof-function mutants that exhibits cleft palate. Information about these knockout models was collected from a literature review 4,21,23,50 and genes were clustered into families of cytokine/receptor, homeobox genes, and miscellaneous (Supplementary Table 1). Out of 84 cleft palate-susceptible genes, expression of 19 of them was up-regulated, and 20 of them were down-regulated significantly in response to consistent nicotine uptake during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lncRNAs have been found to serve a critical role in embryonic development (4), while the dysfunction of lncRNAs is associated with widespread conditions, such as birth defects (5). Cleft palate (CP) is the most common congenital malformation in the oral and craniofacial region, and may occur at any stage of the palate development, including the palatal shelf growth, elevation or fusion (6). In addition, the loss of medial edge epithelial cells or failure of mesenchymal consolidation can cause CP.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of lncRNAs has provided novel opportunities for the investigation of the precise etiology and pathogenesis of CP, which remain unclear. However, although a great number of studies have investigated the underlying mechanisms of TCDD-induced CP (8,14,(16)(17)(18), the involvement of lncRNAs in TCDD-induced CP has been rarely reported (6). lncRNA H19 is a 2,300 bp non-coding RNA (ncRNA), which is transcribed from the maternal allele, with a high expression observed prenatally and a low expression observed postnatally.…”
Section: Introductionmentioning
confidence: 99%